What does an effective institue look like? - Park, D.-H. (3rd International Forum on Elite Sport. Burleigh Court, Loughborough University, 9-11 September 2003, 2003)
Powerpoint-Präsentation über die Forschungsinhalte und Strukturen des "Korea Sport Science Institute".